2009
DOI: 10.1007/s12550-009-0036-9
|View full text |Cite
|
Sign up to set email alerts
|

Field incidence of mycotoxins in commercial popcorn and potential environmental influences

Abstract: Popcorn ear damage by insects and mycotoxin levels in kernels were monitored in several commercial popcorn fields in central Illinois over a 4-year period. Aflatoxin was rare, but fumonisin and deoxynivalenol (DON) were commonly encountered each year, and occurred at mean levels in fields up to 1.7 mg/kg (sample max. 2.77 mg/kg) and 1.9 mg/kg (sample max. 2.66 mg/kg), respectively. Neither fumonisin nor DON levels were significantly correlated with the percent of ears with visibly moldy insect-damaged kernels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Dorn et al (2009Dorn et al ( , 2011 found that the distributions of Fusarium species could not be explained by temperature alone; it was suggested that temperature may not be critical and that other, yet unknown, factors more strongly influence Fusarium prevalence. Dowd and Johnson (2010) working in America, and Goertz et al (2010) in Germany, suggested that local field effects may influence both Fusarium outbreaks and maize mycotoxin levels more than do weather conditions. Additionally, Fusarium species competed when inoculated simultaneously into maize ears (Reid et al 1999) or kernels (Velluti et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Dorn et al (2009Dorn et al ( , 2011 found that the distributions of Fusarium species could not be explained by temperature alone; it was suggested that temperature may not be critical and that other, yet unknown, factors more strongly influence Fusarium prevalence. Dowd and Johnson (2010) working in America, and Goertz et al (2010) in Germany, suggested that local field effects may influence both Fusarium outbreaks and maize mycotoxin levels more than do weather conditions. Additionally, Fusarium species competed when inoculated simultaneously into maize ears (Reid et al 1999) or kernels (Velluti et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also suggest that local effects of the field site may be more important to explain Fusarium infection and mycotoxin concentrations in maize than weather conditions alone. For example, Dowd and Johnson (2010) in the United States and Goertz et al. (2010) in Germany conducted monitoring studies of maize under natural infection.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation on mycotoxin contamination of maize samples collected in Shandong Province at various stages in 2013 and 2014 showed that the incidences and average contents of FBs (FB 1 , FB 2 , and FB 3 ), AF (AFB 1 , AFB 2 , and AFG 1 ), DON, and ZEN increased from harvest stage to storage period, and the authors deduced that the increase in mycotoxin content was caused by fungal growth and reproduction (Wang and others 2016). Investigations also revealed that 100-to 500-fold or greater levels of fumonisin had been detected in insect-damaged maize kernels in comparison with those which were not insect-damaged, while closer to 10-to 30-fold higher levels of DON were determined in insect-damaged versus noninsect-damaged maize kernels (Dowd and Johnson 2010). The cocontamination of foods/feeds with known or unknown mycotoxins is being reported at an increasingly high rate (Stoev and others 2010a, b).…”
Section: Introductionmentioning
confidence: 96%